Mandatory Vaccination for Children by Government in Brazil - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2024)
Taking the cue from the title reported, Brazilian parents of children are obliged from January 2024 to vaccinate their children from 6 months to 5 years with three doses of "Pfizer anti-Covid serum". Anyone who opposes risks losing parental authority: all this happens without the issuance of a law, but through a technical note from the Brazilian Ministry of Health, which has included the anti-Covid vaccine as mandatory for children as previously reported. In this age group, 142 children have died in 3 years of the pandemic, while the total number of Brazilian children is over 18 million, or 0.00025% of the population. Moreover, we do not know if the children who died had other pathologies: in Germany, not a single child died of COVID during the pandemic period ( HTTPS://pubmed.ncbi.nlm.nih.gov/35962242/ ). According to President Lula, "we must criminalize those who do not vaccinate their children". Fines of thousands of euros, loss of state subsidies and even parental authority are foreseen.